Application of Project Based Learning in Teaching Descriptive Writing for Class XI BDP 2 Students at SMK Negeri 9 Samarinda Academic Year 2022/2023 - Wadjir, Wadjir (Educationist: Journal of Educational and Cultural Studies, 2022)
This article aims to see how project-based learning can be applied to teaching descriptive writing to students of SMK Negeri 9 Samarinda. The learning was carried out on 35 students in class XI BDP 2 SMK Negeri 9 Samarinda with an emphasis on project initiation according to students interests and then spesifically focused on how to write descriptive writing as part of the big project. The result shows that through project-based learning, students’ intrinsic motivation could be maintained during the learning process due to two main reason; the existence of project that match their interests in which they could imagine the end result of, and the discussion and brainstorming that not only kept students motivated but also give positive feedback. PBL which is also carried out in descriptive writing also shows that students can acquire the expected 4C skills, namely creativiy, critical thinking, communication, and collaboration. The writing teaching model that focuses on SFV (sensory, figurative, and vivid words) also makes it easier for the students to be able to write in a more structured manner.